Preparation of dahi from buffalo milk and blends with soy milk - Islam, MN; Hossain, MS; Rashid, MH; Siddiki, MSR; Khan, MS; Parvin, F (Bangladesh Journal of Animal Science, 2016)
The present study was conducted to measure the feasibility of using soy milk as a supplement for the preparation of dahi from buffalo milk. In this experiment, four different types of dahi were prepared by partial replacement of buffalo milk with soy milk named A (control-100% Buffalo Milk), B (75% Buffalo Milk + 25% Soy Milk), C (50% Buffalo Milk +50% Soy Milk) and D (25% Buffalo Milk + 75% Soy Milk).The prepared samples were judged by a panel of expert judges for organoleptic qualities and analyzed for chemical tests. From the results of physical study, it was found that the overall organoleptic (viz. smell and taste, body and texture, color and appearance) score of A, B, C and D types dahi varied significantly (P<0.01). From the results of the chemical test, the moisture and protein content increased significantly (P<0.05), while fat, acidity, total solids and mineral contents significantly decreased due to addition of soy milk. From the findings of this work, it was concluded that 25% replacement of buffalo milk with soy milk could be used successfully which would produce dahi nearly similar to the quality of that made exclusively from buffalo milk. Bang. J. Anim. Sci. 2015. 44 (3):137-142